Craftsmen (maistorije), so-called sokalnici and parish priests - Šarkić Srđan (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
Serbian legal sources show us that in the mediaeval Serbia existed different kinds of craftsmen (blacksmiths, woodworkers, tailors, tanners, potters, sadlers, masons, goldsmiths), but not as a free class, rather as a dependent population, close to meropsi (villagers). Beside their handicraft's duties, they were obliged to exercise different services, but their obligations were lesser. Five Serbian Charters and Dušan's Law Code mention so-called sokalnici, a class of people whose legal status has been the object of many discussions and hypotheses. The examination of legal documents shows that the feudal duties of so-called sokalnici were similar to that of villagers, but quantitatively lesser. According to the latest interpretation it seems that sokalnici were villagers who had some 'more elegant and more honourable' duties, connected with the possession of horses. That is the reason why they were completely or partially exempted from some services. Lesser, parish priests, living in villages, were relatively numerous and heterogeneous class that in entirety did not belong to the commoners. However, the legal status of the majority of parish priests was close or identical to the commoners' and that is the reason why we are speaking of them in this paper. Dušan's Law Code makes clearly difference between three groups of parish priests: 1) priests with patrimonial lands (popovi baštinici), who were free; 2) priests who got from their masters three fields were exempted from the feudal sevices, but not from the tributes; 3) priests who got from their masters more than a three fields. They had to exercise the feudal duties according to the law on that eceeding land.